Staircase-Enhanced Magneto-Electric Dipole Antenna for Wideband CP 5G Applications with High-Gain Arrays - Malhat, Hend (2025)
This paper presents a compact magneto-electric dipole (MED) antenna optimized for wideband circularly polarized (CP) radiation for 5G applications. It incorporates a staircase-shaped electric dipole with trimmed corners to excite orthogonal modes for enhanced CP performance. The proposed single-layer MED antenna achieves a 20.6% wide-impedance bandwidth (|₁₁| <−10 dB, 22.97–28.12 GHz) and 21.9% CP bandwidth (<3 dB, 22.23–27.83 GHz) with a compact footprint of 15×15×1.6mm³. There is a symmetrical radiation pattern with a co-to-cross polarization ratio >23 dB and a stable gain of 8.8 dBi. An equivalent circuit model is optimized via particle swarm optimization (PSO). The optimized MED antenna is utilized to investigate various CP-MIMO configurations and wideband sequential arrays. Next, a 1×2 CP-MIMO antenna system is developed, employing polarization diversity in parallel and mirror configurations. Isolation is improved by etching a ground slot between the MED elements, yielding isolation levels of below −20 dB and −23 dB, respectively. Further, a 2×2 CP-MIMO configuration is designed and evaluated. This arrangement demonstrates an envelope correlation coefficient (ECC) of 1×10‾³ and a diversity gain of approximately 10 dB across the operating bandwidth. Finally, a sequential array is designed that applies a 90∘ sequential rotation and phase excitation to MED elements for high-gain CP 5G communications. Here, various array sizes are evaluated, with an 8×8 MED array providing CP radiation (≤1 dB) from 20 to 30 GHz with enhanced impedance and axial ratio bandwidths and stable gain with a peak value of 27.47 dBi.